SENGKETA WARISAN PERUSAHAAN PERORANGAN BERUBAH MENJADI PERUSAHAAN BERBADAN HUKUM - Daniel Kuntjoro Budiman (STIH Putri Maharaja, 2020)
There is a circumstance where some children control an individual company owned by a parent and converted the company into a limited liability company with a loss to the rights of other heirs. The research aims to find on whether a parent’s company is justified or not has been upgraded to a legal entity ignoring other heirs. By using a normative juridical approach, the study is conducted to emphasize the actual facts and analyzed it with applicable regulations. The result shows that it cannot be justified that a limited liability company is established from finances originating of a parent-owned company, since it violates the legitimacy of other heirs’ rights.